La creatividad de la generación Z según su actividad en las redes sociales - Dr. Óscar DÍAZ CHICA,Diana SANTOS FERNÁNDEZ,Dra. Mónica MATELLANES LAZO (Fonseca, Journal of Communication, 2023)
Generation Z is the generation that uses the most social networks and stays online the longest daily. To analyse creativity in social media users, an exploratory qualitative and quantitative study was carried out. The sample, with 40 university students, carried out two experiments adapted from Guilford's alternative uses test to assess divergent thinking and completed a questionnaire.